Neonatal Aeromedical Evacuation During COVID-19: An Interview With Captain Danielle James. Issue 9 (1st September 2021) - James, Danielle; Talbot, Laura A
ABSTRACT: During the coronavirus-19 pandemic, limited information existed about the risks and consequences of severe acute respiratory syndrome coronavirus 2 infection associated with maternal transmission to neonates. With rapidly evolving evidence, Air Force Neonatal Intensive Care Unit nurses at U.S. Naval Hospital Okinawa, Japan, adapted their standard operating procedures to safeguard their at-risk neonatal patients. This interview describes an Air Force NICU nurse's view of neonatal transport and nursing care during the coronavirus-19 pandemic.